Negara Hukum Indonesia: Esensi Perlindungan Hak Asasi Manusia dalam Pembentukan Peraturan Perundang-Undangan - Akmal, Diya Ul (Primagraha Law Review, 2023)
The social life of the community contains a wedge of rights breaches committed both by individuals and by the state. Thus, the requirement for rights protection in the establishment of laws and regulations is affirmed. Law is the basis for the State of Law in social and state life. The establishment of laws and regulations is supposed to restrain excessive state authority and create limitations for each individual so that they do not violate the rights of others. The current State of Law paradigm has stressed the protection of Human Rights as being complementary in the functioning of society and the state. This is inextricably linked to the crucial role of Human Rights as natural rights that must be maintained and defended by all individuals and states. The protection of Human Rights has been made a part of the rights guaranteed by amendments of the 1945 Constitution of the Republic of Indonesia. Legislation programs in the establishment of laws and regulations must be oriented to be in conformity with Pancasila, the 1945 Constitution of the Republic of Indonesia, the National Medium-Term Development Plan, and must satisfy aspects of Human Rights protection. As a result, it is hoped that the goal of establishing laws and regulations that bring justice and benefits to the community would be realized in the development of the Indonesian State of Law.